Analisis Strategi Diplomasi Vaksin Multijalur Indonesia dalam Upaya Mengatasi Pandemi Covid-19 2020-2021 - Dipta Harizqi (Universitas Sulawesi Barat, 2022)
Since the beginning of 2020, the Covid-19 pandemic has become a global threat. Each country is making various collaborative efforts to be able to overcome the problems of the Covid-19 pandemic. During this pandemic, Indonesia is one of the countries that is active in building cooperative relations. This was proven when Indonesia implemented its vaccine diplomacy strategy. Vaccine diplomacy is a cooperative strategy carried out by Indonesia during the Covid-19 pandemic. In its application, vaccine diplomacy is carried out in a multi-track manner which places the state no longer as the main actor. Vaccine diplomacy carried out certainly has a variety of objectives. In addition to securing the availability of many vaccines, this strategy has a goal in fighting for fair and equitable access to health. Thus, there is no longer a potential gap between countries in seeing the problems of the Covid-19 pandemic. This study uses a descriptive qualitative method that analyzes Indonesia's multi-lane vaccine diplomacy strategy in an effort to overcome the Covid-19 pandemic (2020-2021). This research shows that, through its vaccine diplomacy strategy, Indonesia has succeeded in building multi-channel cooperation which then includes cooperation between the government and the government, the government and the private sector, the government and international organizations, and of course this shows significant results.